Action-image: formulations of spacialities in “body configurations” by VALIE EXPORT (Palíndromo, 2020)
The article focuses on VALIE EXPORT’s series of photoperformance “Body Configurations” (1972-1976), assuming the body as object and sentient for artistic practice in space. It is proposed to think the artist’s formulations as a phenomenological construction, evidencing the reorganization of her body as an active and critical element of urban design. These are anxieties that establish a clash of the body in the city model modeled by the corporeal limits and as resistance to power, in what we understand photoperformances as “image-action.”
Keywords: action-image; photoperformance; bodyperception; contemporary art; VALIE EXPORT